Analysing twenty-first century British English : conceptual and methodological aspects of the Voices project - Upton, Clive, 1946-; Davies, Bethan L. (Milton Park, Abingdon, Oxon : Routledge, 2013)
'The Voices project of the British Broadcasting Corporation, a recent high-profile media investigation, gathered contemporary English dialect samples from all over the UK and invited contributions from the public to a dedicated website. This book explores both issues of ideology and representation behind the media project and uses to which the emerging data can be put in the study of language variation and change. Two lead-in chapters, written from the complementary perspectives of a broadcast media specialist, Simon Elmes, and an academic linguist, David Crystal, set the project in the BBC's historical, social, and linguistic contexts. Following these, authorities in a range of specialisms concerned with uses and representations of language varieties address various aspects of the project's potential, in three broad sections: Linguistic explorations of the representations of language and the debates on language evoked by the data. ; The linguistic product of the project, including lexical, phonological, and grammatical investigations. ; Technical aspects of creating maps from the large electronic Voices database. An interactive companion website provides the means to access, explore, and make use of raw linguistic data, along with interpretive maps created from it, all accompanied by full explanations. Analysing 21st Century British English brings together key research and is essential reading for advanced undergraduate students, postgraduate students and researchers working in the areas of language variation, dialect and sociolinguistics.'--Publisher's website.
Voices: a unique BBC adventure / Simon Elmes -- Voices: a case study in the evolution of a linguistic climate at the BBC / David Crystal -- Constructions of expertise and authority on a language-themed discussion forum: linguists, linguistics and the public / Bethan L. Davies -- Diverse Voices, Public Broadcasts: sociolinguistic representations in mainstream programming / Alexandra Jaffe -- Afrikaans is bobaas: Linguistic citizenship on the BBC Voices website / Tommaso M. Milani and Mooniq Shaikjee -- Language Ideology and Conversationalized Interactivity in Voices / Will Turner -- Mapping the Word: Local Vocabulary and its Themes / Susie Dent -- Voices in Wales: a new national survey / Rob Penhallurick -- Voices of the UK: The British Library description of the BBC Voices Recordings collection / Jonathan Robinson, Jon Herring, and Holly Gilbert -- Focus on voices in North-east England / Ann Thompson -- Blurred Boundaries: the dialect word from the BBC / Clive Upton -- Voices dialectometry at the University of Sheffield / John Holliday -- Voices dialectometry at the University of Groningen / Martijn Wieling.
Includes bibliographical references and index.
Keywords: British Broadcasting Corporation -- History -- 21st century; English language -- Dialects -- United Kingdom; English language -- Variation -- United Kingdom; English language -- Great Britain -- Discourse analysis; English language -- Great Britain -- Phonology; English language -- Social aspects -- United Kingdom; English language -- Syntax; United Kingdom. -- Languages